Assessment of the Suitability of Pitanga Leaf Extract as a Natural Antioxidant for Enhancing Canola Oil Stability: Monitoring Lipid Oxidation Parameters. Issue 5 (27th February 2019) - Vargas, Flávia C.; Gómez, Belen; Mousavi Khaneghah, Amin; Strozzi, Isabella; Gavahian, Mohsen; Barba, Francisco J.; Sobral, Paulo José do Amaral; Lorenzo, Jose M.
Abstract : The efficiency of pitanga leaf extracts (PLE) to protecting vegetable oils against lipid oxidation is evaluated and compared with the synthetic antioxidant butylated hydroxytoluene (BHT). In addition, the main phenolic compounds and antioxidant properties of PLE are determined by UPLC‐DAD‐MS/MS and spectrophotometric methods. Moreover, the fatty acid composition and lipid oxidation of canola oil containing five different concentrations of PLE (200–1000 ppm), BHT or without added antioxidant are evaluated after being subjected to accelerated oxidation conditions (60 °C during 16 days). The results show a considerable amount of phenols (229.4 mg gallic acid/g extract) with two major phenolic compounds (miricitrin and quercetin 3‐α‐fucopiranoside) in the PLE intermediate fraction. The fatty acid composition of canola oils with additives did not change significantly after 16 day of accelerated oxidation (7.3% SFA, 64.5% MUFA, and 27.8% PUFA). The incorporation of PLE, even at the minimum concentration assayed (200 ppm), offers important decreases of primary and secondary oxidation products with respect to the control sample, obtaining reduction percentages of 74, 58, 62, and 61% for peroxides, conjugated dienes, p‐anisidine, and TBARS values, respectively. A similar stability for canola oil is observed with BHT at equivalent concentrations, enhancing the inhibitory effects against lipid oxidation in different oxidations steps. Practical Applications : The incorporation of pitanga leaf extracts to canola oils is a promising strategy to preserve their polyunsaturated fatty acids, avoiding their lipid oxidation during storage. This procedure is of great interest due to the natural origin of the additive under study versus synthetic antioxidants like butylated hydroxytoluene. The antioxidant potential of pitanga leaf extracts, including UPLC‐DAD‐MS/MS phenolic profile, antioxidant activities, and their effects on canola oil stability after accelerated storage conditions, are evaluated. Abstract : The antioxidant potential of pitanga leaf extracts, including UPLC‐DAD‐MS/MS phenolic profile, antioxidant activities, and their effects on canola oil stability after accelerated storage conditions, are evaluated.